ATTITUDES, PREFERENCES, AND CHARACTERISTICS OF OHIO'S SPRING TURKEY HUNTERS, 1985–2001 - David A. Swanson; Robert J. Stoll Jr.; W. Lloyd Culbertson (Wildlife Society Bulletin)
Abstract: The popularity of spring wild turkey (Meleagris gallopavo) hunting in Ohio increased since the first modern season in 1966. As hunter numbers increased, so have problems and issues with managing the spring hunt. Random samples of Ohio spring turkey hunters were mailed a questionnaire immediately following the 1985, 1989, 1996, and 2001 spring turkey seasons. The questionnaire responses were used to determine the attitudes, preferences, and concerns of Ohio spring turkey hunters regarding wild turkey management and turkey hunting. Over 66% (±3%) of 1985, 70% (±3%) of 1989, 80% (±3%) of 1996, and 85% (±2%) of 2001 turkey hunters reported they had spring turkey hunted in Ohio ≥2 years. As in 1989 and 1996, >95% (±2%) of turkey hunters reported using a shotgun during the 2001 Ohio spring turkey season. Use of decoys by spring turkey hunters increased from 14% (±2%) in 1989 to 67% (±3%) in 2001. The percentage of hunters hunting mostly on public land decreased from 32% (±3%) in 1989 to 19% (±3%) in 2001. The total estimated expenditures by spring turkey hunters during the 2001 season was $14.9 million compared to $5.8 million in 1996 and $2.1 million in 1989. Hunters consistently ranked uninformed hunters and overcrowded hunting conditions as the most serious problems affecting turkey hunting safety. The percentage of turkey hunters who considered disturbance by other hunters a “big” problem decreased from 26 (±3%) to 14% (±2%) between 1985 and 2001. However, almost 60% (±3%) of the 2001 turkey hunters reported they were concerned about being shot by another hunter and 38% (±3%) indicated they had another hunter sneak up on them while turkey hunting. Although most (72 ± 3%) hunters indicated they never wore hunter orange at all times, 26% (±3%) reported they always wore hunter orange when moving and 42% (±3%) always carried their harvested bird in orange covering when walking out of the woods. Public education on hunting safety was ranked the most important turkey management activity by 1996 and 2001 turkey hunters. Over 85% (±2%) of hunters ranked high gobbling activity as the primary factor contributing greatly to enjoyment of the spring turkey hunting experience, followed by killing an adult turkey (71 ± 3%) and calling turkeys (69 ± 3%). The composite Ohio spring turkey hunter was male, 49 years old, had a rural background, and a total household income >$50,000. Ohio spring turkey hunters had hunted for an average of 28 years, but had spring turkey hunted for <10 years.